Pengaruh Tingkat Suku Bunga Dan Inflasi Terhadap Permintaan Kredit Usaha Mikro Kecil Menengah Di Kalimantan Timur - Edma Syahyunita Samad; Aji Sofyan Effendi; Juliansyah Roy (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to determine the effect of interest rate and inflation rate against loan demand Micro Small and Medium in the province of East Kalimantan. The data used in this research is secondary data within a period of ten years from the period 2006 to 2015. This study was analyzed using multiple linear regression analysis tools. Existing data were processed using SPSS (Statistical Package for Social Science) version 21. Analysis showed that the level of interest rates and a significant negative effect on credit demand, while inflation is negative and no significant effect on credit demand.